Development of a Model for Functional Studies of ABCG2 (Breast Cancer Resistance Protein) Efflux Employing a Standard BeWo Clone (B24) - Crowe, Andrew; Keelan, J. (Mary Ann Liebert, 2012)
Human choriocarcinoma-derived BeWo cells express high levels of breast cancer resistance protein (BCRP/ABCG2) with no functional P-glycoprotein (P-gp) (ABCB1) activity, making them a potential model to study bidirectional ABCG2-mediated drug transport. However, the original BeWo clone (B24) available to researchers does not form confluent monolayers with tight junctions required by the model. Our aim was to adapt culture conditions to attempt to generate confluent BeWo monolayers for drug transport studies using the standard B24 clone. BeWo cells (B24; American Type Culture collection [ATCC]) were cultured in six-well plates or polycarbonate millicell inserts in a number of media formulations, growth supplements, and basement membrane substitutes. Cells were examined for confluence by microscopy, and transepithelial electrical resistance (TEER) was measured daily; monolayer permeability was assessed when TEER had stabilized. Optimal growth rates were achieved in culture conditions consisting of Medium 199 (M199) supplemented with epidermal growth factor (EGF; 20 ng/mL), vitamin supplements, and 10% fetal calf serum (FCS) with collagen coating. A TEER of 170 Ω in 0.6 cm2 inserts was achieved 2 weeks after seeding under optimal conditions. The cell-impermeable diffusion marker 5(6) carboxy-2,7dichlorodihydrofluorescein (C-DCDHF) had a permeability coefficient of 3.5 x 10-6 cm/s, indicative of minimal paracellular permeability. ABCG2 expression, as determined by immunoblotting, remained unaffected by confluency. In conclusion, we describe culture conditions for the B24 BeWo clone that facilitate the formation of monolayers with tighter junctions and reduced paracellular transport compared to previously published models. These growth conditions provide a good model of ABCG2-mediated drug transport in a human placental cell line.